2008
DOI: 10.1002/eji.200838278
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin impairs humoral and cell‐mediated immunity in mice by inhibiting lymphocyte homing, T‐cell activation and antigen cross‐presentation

Abstract: Statins block the activity of HMG-CoA reductase, which catalyses the production of mevalonate, an intermediate in cholesterol biosynthesis, which is also a precursor of isoprenoids. In addition to lowering circulating cholesterol, these drugs display antiinflammatory and immunomodulatory activities in vitro; however, their effects on the development of adaptive immune responses in vivo, as well as the underlying mechanisms, are as yet largely unknown. Here we investigated the outcome of simvastatin treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
(72 reference statements)
1
12
0
2
Order By: Relevance
“…Previous in vivo and in vitro studies have shown that modification of the innate and acquired immune responses by statins contributes to their anti-inflammatory properties via decreased adhesion molecule expression, antigen presentation, cytokine production, receptor signaling and T-cell activation and proliferation. 11,19,20 This study has confirmed that AT slows the development of TCAD, as well as allograft CD4 ϩ T cells and macrophage recruitment. Previous studies, by our group and others, have reported that CD4 ϩ T cells and macrophages play a pathogenic role in the development of TCAD in this model system.…”
Section: Discussionsupporting
confidence: 85%
“…Previous in vivo and in vitro studies have shown that modification of the innate and acquired immune responses by statins contributes to their anti-inflammatory properties via decreased adhesion molecule expression, antigen presentation, cytokine production, receptor signaling and T-cell activation and proliferation. 11,19,20 This study has confirmed that AT slows the development of TCAD, as well as allograft CD4 ϩ T cells and macrophage recruitment. Previous studies, by our group and others, have reported that CD4 ϩ T cells and macrophages play a pathogenic role in the development of TCAD in this model system.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, it was previously reported that cyclosporin A and tacrolimus, which are the principal drugs used to suppress transplantation rejection, profoundly inhibit the class I and class II MHC-restricted presentation of antigenic peptides both in vitro and in vivo, suggesting that the immunosuppressive activity of cyclosporin A and tacrolimus is at least in part due to the inhibition of the antigen processing pathways [10][11][12]. Simvastatin, an inhibitor of HMG-CoA reductase which is a major rate-limiting enzyme in the cholesterol biosynthesis pathway, has also been reported to inhibit the class I MHC-restricted presentation of exogenous antigen [13]. Inhibition of MHC-restricted antigen presentation has also been reported on nonsteroidal anti-inflammatory drugs such as aspirin and ibuprofen [14].…”
Section: Introductionmentioning
confidence: 96%
“…O reconhecimento, ativação e expansão clonal pelos linfócitos é essencial para uma resposta imune adaptativa eficaz 32 . Sabe-se que a sinvastatina age sobre o sistema imunológico inato e adquirido, regulando a ativação de neutrófilos, macrófagos, da resposta imune celular (Th1), humoral (Th2), diminuindo a migração de células T e B para os órgãos linfóides secundários (baço, linfonodos) e de leucó-citos para o sangue periférico, e a apresentação de antígenos via MHC de classe I e II 6,[33][34][35][36][37] . A migração dos linfócitos para os locais de infecção e órgãos linfoides secundários é governada pela adesão de moléculas, uma delas é a LFA-1 (antíge-no 1 associado a função do linfócito), esta quando associada ao ligante ICAM-1 aumenta a adesão dos linfócitos a paredes dos vasos 6 .…”
Section: Discussionunclassified
“…Linfonodos cervicais fazem parte dos órgãos linfoides periféricos e participam da imunidade adaptativa, os antígenos são apresentados aos linfócitos pelas células apresentadoras de antígenos e proteínas do maior complexo de histocompatibilidade, iniciando assim a ativação de linfócitos e expansão clonal 6 . As estatinas são inibidores da 3-hidroxi -3-metilglutaril coenzima A reductase (HMG-CoA) uma enzima que catalisa a produção do melavonato, o colesterol é um dos produtos desta via e a interrupção da mesma leva a queda dos níveis lipídicos, além disso, apresenta propriedades anti-inflamatórias e imunomoduladoras 7 . Estudos têm mostrado que a sinvastatina pode ser usada como agente imunomodulador da ação inflamatória, com potenciais implicações terapêuticas no tratamento de doenças inflamatórias crônicas [8][9][10][11] .…”
Section: Introductionunclassified